Handbook of Plastic Foams - Landrock, Arthur H. (Noyes Publications, 2011)
This book is intended to be a source of practical information on all types of plastic foams (cellular plastics) in use, including the new structural plastic foams. Elastomer (rubber-like) foams are also considered.